1999
DOI: 10.1164/ajrccm.160.1.9809048
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-induced Eosinophil Cytolysis Is a Primary Mechanism for Granule Protein Release in Human Upper Airways

Abstract: Cytotoxic eosinophil granule proteins are considered important in the pathogenesis of allergic airway diseases such as rhinitis and asthma. To explore the cellular mechanisms behind eosinophil granule release in human allergic airways, 16 symptom-free patients with seasonal allergic rhinitis were challenged daily with allergen during 1 wk. Nasal lavage samples and biopsies, obtained before and 24 h after the last allergen exposure, were processed for immunohistochemical and electron microscopic analysis. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
93
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 37 publications
3
93
1
1
Order By: Relevance
“…The accumulation of eosinophils, especially intraepithelial eosinophils, the detection of extracellular granules, and epithelial cell hyperplasia mimic the pathophysiological changes observed in individuals with various forms of eosinophilic esophagitis (6). Of note, the detection of protein-laden free eosinophil granules is a common pathological observation in human eosinophilic inflammation (33). It is likely that sensitization occurs by pulmonary exposure, since oral or intragastric allergen exposure alone fails to elicit eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of eosinophils, especially intraepithelial eosinophils, the detection of extracellular granules, and epithelial cell hyperplasia mimic the pathophysiological changes observed in individuals with various forms of eosinophilic esophagitis (6). Of note, the detection of protein-laden free eosinophil granules is a common pathological observation in human eosinophilic inflammation (33). It is likely that sensitization occurs by pulmonary exposure, since oral or intragastric allergen exposure alone fails to elicit eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of these granules had a preserved core structure, suggesting that they were released as intact granules. These ultrastructural features, mainly eosinophil cytolysis and the release of free proteinladen eosinophil granules, are the most common finding associated with eosinophilic mucosal inflammation in human disorders (32,33).…”
mentioning
confidence: 99%
“…Preliminary results already suggest that eosinophils, occurring in the target tissue during active seasonal allergic rhinitis, may exhibit more pronounced degranulation than in many other common diseases characterised by tissue eosinophilia, e.g. inflammatory bowel disease and asthma [8,9]. However, as yet, little is known about the dynamics of eosinophil degranulation in allergic rhinitis, especially when the disease progresses from a nonsymptomatic baseline situation into an active symptomatic condition.…”
mentioning
confidence: 99%
“…Another goal was to establish the baseline degranulation status in nonsymptomatic patients. Thus, a transmission electron microscopic (TEM) detailed analysis was employed to assess the level of eosinophil degranulation in allergic rhinitis before and during seasonal allergen exposure [9,10]. Also, the occurrence of eosinophil cationic protein (ECP) in nasal tissues and lavage fluids was determined.…”
mentioning
confidence: 99%
“…43 ECP plays an important role in the pathogenesis of URT allergic inflammation 11 and asthma, where it is released in response to allergen-immunoglobulin E (IgE) crosslinking. 14 Recently, it was reported that a dietary deficiency of antioxidant vitamins may play a role in increasing the severity of asthma. 24 Bowler amd Crapo 6 suggested that augmentation of existing antioxidant defences with catalytic antioxidants might be useful in attenuating respiratory disorders through counteracting the effects of inflammatory cells such as airway eosinophils.…”
Section: Discussionmentioning
confidence: 99%